Portugueses no Brasil: migrantes em dois atos - Kushnir, Beatriz (Revista Maracanan, 2014)
MARTINS, Ismênia de Lima; SOUSA, Fernando (org.). Portugueses no Brasil: migrantes em dois atos. Niterói: Muiraquitã, 2006. 300p